Trends in dietary carbohydrate consumption from 1991 to 2008 in the Framingham Heart Study Offspring Cohort - Makarem, Nour (2014)
The intake of carbohydrates has been evaluated cross-sectionally, but not longitudinally in an ageing American adult population. The aim of the present study was to examine trends in the intake of dietary carbohydrates and their major food sources among the Framingham Heart Study Offspring (FOS) cohort, which had been uniquely tracked for 17 years in the study. The FOS cohort was recruited in 1971–1975. Follow-up examinations were conducted, on average, every 4 years. Dietary data collection began in 1991 (examination 5) using a validated semi-quantitative FFQ. The study included 2894 adults aged ≥25 years with complete dietary data in at least three examinations from 1991 to 2008. Descriptive statistics were generated using SAS version 9.3, and a repeated-measures model was used to examine trends in the intake of carbohydrates and their food sources in the whole sample, and by sex and BMI category. Over 17 years of follow-up, the percentage of energy from total carbohydrates (51·0–46·8 %; P for trend<0·001) and total sugars (18·2–16·6 %; P for trend<0·001) decreased. There was a decrease in the percentage of energy from fructose (5·4–4·7 %; P for trend<0·001) and sucrose (9·8–8·8 %; P for trend<0·001). Dietary fibre intake increased (18·0–19·2 g/d; P for trend<0·001). The number of weekly servings of yeast bread, soft drinks/soda, cakes/cookies/quick breads/doughnuts, potatoes, milk, pasta, rice and cooked grains, fruit juice/drinks, potato chips/maize chips/popcorn, and lunch foods (e.g. pizzas and burgers) decreased significantly (P for trend<0·001), while the intake of ready-to-eat cereals, legumes, fruits, dairy products, candy and ice cream/sherbet/frozen yogurt increased significantly (P for trend<0·04). Similar trends were observed when the analyses were stratified by sex and BMI. The present results suggest favourable trends in dietary carbohydrate consumption, but dietary guidelines for fruits, vegetables and fibre were not met in this cohort.